A new approach for investigating corrugated laminated composite plates of wave form - Bich, Dao Huy; Phu, Khuc Van (Vietnam Journal of Mechanics, 2008)
Corrugated plates of wave form made of isotropic elastic material were considered as flat orthotropic plates with corresponding orthotropic constants determined empirically by the Seydel’s technique. In some recent researches the extension of this technique was given for corrugated laminated composite plates. In the present paper a new approach for investigating corrugated composite plate of wave form is proposed, regarding this plates as a combination of parts of shallow cylindrical shells with alternative curvatures. It reduces to no use of Seydel’s empirical formulas and sufficiently apply to composite plates. Based on this approach governing equations of corrugated laminated composite plate of wave form are developed and application to the non-linear stability problem of this plate is considered. Obtained results are compared with those of Seydel’s technique